High dose cyclophosphamide for cytoreduction in patients with acute myeloid leukemia with hyperleukocytosis or leukostasis. Issue 5 (16th April 2021) - Zhao, Jennifer; Bewersdorf, Jan Philipp; Jaszczur, Sara; Kowalski, Andrew; Perreault, Sarah; Schiffer, Molly; Gore, Steven; Podoltsev, Nikolai; Prebet, Thomas; Shallis, Rory; Zeidan, Amer M.
Abstract: Hyperleukocytosis may lead to multiple medical emergencies. Hydroxyurea, intensive chemotherapy, and leukapheresis are used for cytoreduction. However, there is little data regarding the best approach. Here, we report on the efficacy and safety of high dose cyclophosphamide (HDCy; 60 mg/kg). 27 patients with acute myeloid leukemia or blast phase chronic myeloid leukemia who presented with white blood cell count (WBC) of ≥50x10 9 /L or symptoms of leukostasis were treated with HDCy. Primary endpoint was early mortality (death within seven days of admission). Median WBC was 107 × 10 9 /L at time of HDCy; 74% had leukostasis symptoms at presentation. Eight (29.6%) patients died within seven days of admission. Sustained WBC reduction was achieved in 18/24 (75%) evaluable patients with median nadir of 0.25 × 10 9 /L. Adverse effects attributed to HDCy included tumor lysis syndrome ( n  = 7; 25.9%), disseminated intravascular coagulopathy ( n  = 5; 18.5%), and hemorrhagic cystitis ( n  = 1; 3.7%). HDCy was effective for cytoreduction and adverse effects were acceptable.